Ensuring the citizens’ rights as a priority area of police activity in Ukraine (on the example of the information subsystem "CUSTODY RECORDS" functioning) (Law and Safety, 2021)
The current stage of police bodies’ activity to ensure the rights and freedoms of citizens has been described. It is emphasized that, given the current stage of updating approaches to the organization of police bodies and units, it is important to ensure the observance of citizens' rights in police activities, to prevent illegal actions either by both police officers or toward police officers.It is established that the main purpose of the information subsystem "CUSTODY RECORDS" is to create conditions for the implementation of internationally recognized standards for the protection of the rights of detainees. On the example of the functioning of the information subsystem "CUSTODY RECORDS" the peculiarities of ensuring the observance of citizens' rights in the activities of police officers, prevention of illegal actions either by both police officers or toward police officers have been analyzed. Features of the information subsystem "CUSTODY RECORDS" have been revealed.It is established that the introduction of the information subsystem "CUSTODY RECORDS" has highlighted the need for quality training of police officers responsible for detainees in the police department and respect for human rights. As a result of the description of the process of training human rights inspectors, which consists of three blocks, it has been concluded that during such training the main attention is paid to studying the algorithms of police actions to prevent violations of human rights and freedoms during his stay in the police station. detentions, torture and psychological pressure on police detainees, prevention of suicide and self-harm.Proposals for amendments to regulations the provisions of which govern the activities of patrol police, inspectors on duty, investigators, in terms of determining the scope of their powers to work with the information subsystem "CUSTODY RECORDS" are formulated. It is emphasized the importance of enshrining at the legislative level the procedures for data protection contained in the information subsystem "CUSTODY RECORDS", and the introduction of a system of control over the processes of data collection and storage.
Keywords: police; police officers; citizens' rights; protection of detainees' rights; illegal actions; «CUSTODY RECORDS» information subsystem